Idol food in Corinth : Jewish background and Pauline legacy - Cheung, Alex T. (Alex Tat-Man), 1960- (Journal for the study of the New Testament. Supplement series, 1999)
This historical and exegetical investigation strongly challenges the widely held view that Paul regarded idol food as a matter of indifference, to be avoided only for the sake of the spiritual health of the weak. An exhaustive treatment of early Christian material shows that early authors were deeply influenced by Paul's discussion in 1 Corinthians 8-10, and yet they were totally unaware of the subsequent traditional understanding that Paul regarded idol food as indifferent. Even those who advocated eating idol food did not once appeal to Paul's discussion for support. An alternative understan.